The promise [large type] : a novel - Walsh, Dan, 1957- (Walsh, Dan, 1957- Restoration series, 2014)
For the last five months, Tom Anderson has been without a job, a fact he's been hiding his wife Jean and everyone else. He leaves each morning pretending nothing has changed and spends his day rotating through two coffee shops and the library, using their wi-fi to search for a job on the internet. The stress of Tom's secret is putting serious strain on his marriage and it looks like the legacy that began with his father is still at work, slowly destroying the bond between Tom and Jean. Can their mutual trust -- and love -- be restored?